THU0544 Auditing the Impact of the Application of the Proposed New 2014 International Criteria for Behçet's Disease. (9th June 2015) - Mitton, D.; Blake, T.; Carruthers, D.; Damato, E.; Denniston, A.; Poveda-Gallego, A.; Hamburger, J.; Murray, P.I.; Powell, S.; Richards, A.; Sewell, V.; Situnayake, D.
Abstract : Background: As there is no diagnostic test for Behçet's Disease (BD), multidisciplinary assessment remains the gold standard for diagnosis In 2014, an international team from 27 countries (not including the UK), described the New International Criteria for Behçet's disease. The Criteria were judged capable of "performing with good discriminatory potential (Sensitivity 94.8%, ISG 85%, specificity 90.5%, ISG 96%) regardless of country" and were felt to be "intuitive and easy to use in a wide variety of settings" [1]. The authors suggessted a role for for mass screening and identification of possible BD Objectives: To assess the performance of the proposed new international criteria for Behcets Disease in a UK setting. Methods: The following information was captured from the cohort: Patient demographics Frequency distribution of clinical characteristics of BD for patients with clinically confirmed BD, incomplete BD and a rejected diagnosis of BD. The proposed 2014 ICBD criteria were compared with the ISG 1990 in comparison to the gold standard multidisciplinary assessment at the Birmingham National Centre. Results: There were 80 females and 39 males. 16 cases were clinically diagnosed following multidisciplinary review but failed to meet ISG 1990 criteria. All of these met the ICBD 2014 criteria. 12 cases were ISG+ but BD was not confirmed clinically (including 3 clinically rejected BD diagnosis). This increased to 14 cases for the ICBD 2014 criteria (including 5 clinically rejected BD diagnosis) Conclusions: As expected the proposed ICBD 2014 criteria were more sensitive at picking up cases than ISG 1990 using the multidisciplinary assessment process as the gold standard Specificity was less than expected for both criteria, as in our hands some clinical features were not always judged either to be attributable to a possible BD diagnosis or confidently ascertained, though time and future follow up may improve performance. A more detailed expert gynaecology assessment has now been factored into service design Those patients with "Incomplete BD" form an interesting subgroup which may warrant more detailed examination e.g. those patients who present with posterior uveitis consistent with BD but fail to fulfil the classification criteria. Routine use of pathergy testing may enhance performance. ICBD may serve as a useful screening tool but in our hands in a mainly UK population (62% white British) may over diagnose BD Patients referred to the National Behçets Centres. Our three national centres represent an ideal setting to extend our study. References: International Team for the Revision of the International Criteria for Behçet's Disease (ITR-ICBD). The International Criteria for Behçet's Disease (ICBD): a collaborative study of 27 countries on the sensitivity and specificity of the new criteria. J Eur Acad Dermatol Venereol 2014;28:338-47. Disclosure of Interest: None declared